A tocotrienol series with an oxidative terminal prenyl unit from Garcinia amplexicaulis. (January 2015) - Lavaud, Alexis; Richomme, Pascal; Gatto, Julia; Aumond, Marie-Christine; Poullain, Cyril; Litaudon, Marc; Andriantsitohaina, Ramaroson; Guilet, David
Graphical abstract: Ten tocotrienol derivatives were isolated from stem bark of Garcinia amplexicaulis together with eleven known compounds. Some dimeric tocotrienol derivatives exhibited unprecedented modes of connection of the two monomeric moieties. The compounds showed significant antioxidant activities. Highlights: Study of Garcinia amplexicaulis, an endemic Clusiaceae species from New Caledonia. Isolation and identification of ten new tocotrienol derivatives. Two dimeric tocotrienol derivatives with unprecedented modes of connection. One of the highest degrees of structural tocotrienol diversity in angiosperms. Evaluation of their antioxidant activities (TBARS and ORAC assays). Abstract: Ten tocotrienol derivatives, i.e., amplexichromanols (1 –10 ), were isolated from stem bark of Garcinia amplexicaulis Vieill. ex Pierre collected in Caledonia. The structures of the compounds1 –5 were determined to be chromanol derivatives substituted by a polyprenyl chain oxidized in terminal position. The remaining compounds6 –10 are the corresponding dimeric derivatives. Eleven known compounds, including xanthones, tocotrienol derivatives, triterpenes and phenolic compounds, were also isolated. Their structures were mainly determined using one and two-dimensional NMR and mass spectroscopy analysis. The compounds and some amplexichromanol molecules formerly isolated from G. amplexicaulis exhibited significant antioxidant activity against lipid peroxidation and in the ORAC assay.